Przydatność technologii informatycznych w analizie portfelowej - Golik-Górecka, Grażyna (Usefulness of Information Technologies in Portfolio Analysis, 2006)
The aim of this article is a presentation of initial research study using portfolio analysis in practical implementation of enterprise. There are classical portfolio analysis or their modem models. Moreover, this article particularly focuses on possibilities of using computer applications for example Bunch of ZSP or BI of IFS in portfolio analysis and the realization of marketing strategies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 633-639